Autoantibodies and Vitamin Levels: Is A Player Or Not in Pathophysiology of Multiple Sclerosis Patients? - Turkoglu, Sule Aydin; Ogun, Muhammed Nur; Karabork, Seyda; Yildiz, Serpil; Yildiz, Nebil (Archives of Clinical and Biomedical Research, 2018)
Introduction and Aim: Multiple sclerosis is a demyelinating autoimmune disease of the central nervous system. ANA, anti-dsDNA, and ENA profiles have been used in the diagnosis and treatment of autoimmune diseases. Low vitamin D and B12, and folate levels, and high homocysteine levels are often detected in autoimmune diseases. In the present study, we aimed to investigate these parameters in patients with Multiple sclerosis and Multiple sclerosis like disease, as diagnosed in accordance with the revised McDonald criteria. Methods: The laboratory results of 161 (53Multiple sclerosis, 108 Multiple sclerosis like) patients who were examined for the differential diagnosis of vasculitis/Multiple sclerosis in the last 14 months were evaluated in this present retrospective, cross-sectional study. ANA, anti-dsDNA, ENA profile, vitamin D and B12, folic acid, and homocysteine levels were recorded. Results: ANA levels in 12 patients with Multiple sclerosis and in 34 patients with Multiple sclerosis like disease were positive; however, ANA levels were negative in 37 patients Multiple sclerosis, and 72 patients with Multiple sclerosis like disease. Anti-dsDNA levels in 4 patients Multiple sclerosis and in 23 with Multiple sclerosis like disease were positive; however, they were negative in 44 patients with Multiple sclerosis and 81 with Multiple sclerosis like disease. The mean vitamin B12 and D, and folate levels of 111 patients were found below the lower normal limit, whereas PTH and homocysteine levels were found over the upper normal limit. Conclusion: The present study was the first to report the autoimmune parameters and vitamin D levels in patients with Multiple sclerosis and Multiple sclerosis like disease in Bolu province in the Western Black Sea region. Although ANA positivity comes to the forefront in the diagnosis of autoim